Produção de etanol e hidrolisado de levedura utilizando sorgo sacarino [Sorghum bicolor (L.) Moench] como matéria-prima - Pasqual, Thiago Murilo (2013)
Ethanol is an environmentally and economically viable biofuel in Brazil, where its use has largely replaced fossil polluting fuels in vehicles. However, due to agronomic issues, it presents a very big off-season, causing a drop in production, rising costs and prices in the industries and loss of market for gasoline. Alternative raw materials to sugar cane are being studied to reduce this gap and increase domestic production of ethanol. The sweet sorghum is emerging as one of these options due to its ease of planting, harvesting ability during sugarcane offseasons and good yield in the formation of sugars in the stem and seeds. This project aimed at studying the fermentation of sorghum, evaluating the possibility of hydrolysis of the starch present in the seeds and the direct fermentation of the broth originated from the stalks. A process for the use and processing of the biomass generated during fermentation, which originates a yeast extract rich in amino acids, was also investigated. The first stage of the study was to obtain, characterize and process the juice obtained directly from the stems of sweet sorghum. After grinding, filtering and fermenting the broth, the alcohol content and the yields obtained with various commercial strains (CAT-I, PE-II, BG-I e SA-I) were evaluated. The second stage of the work was the study of acid and enzymatic hydrolyses of the starch present in the plant seeds, as well as subsequent fermentation. Finally, the last step consisted in processing the biomass produced in the fermentation, in order to obtain free amino acids through the hydrolysis of yeast. As a result, a broth with 144 g/L of total sugars was obtained from the stems with a production of 47,20 g/L ethanol, which represents a yield of 73,33%. In the acid hydrolysis of starch, the temperature was the most important variable for the process, with best yields obtained at 120ºC. 93,97 g/L of reducing sugars were obtained after acid hydrolysis and then 29,24 g/L of ethanol, representing a yield of 61,02%. With the enzymatic hydrolysis 52,80 g/L of ethanol were produced representing a yield of 73,44%. The utilization of sorghum seed as a source of sugars for fermentation would render an increase of 38% in ethanol production per hectare. With respect to the use of yeast, it was found that the methods of breaking the cell wall by autolysis, proteolysis, mechanic rupture and alkaline hydrolysis were effective in the release of compounds having the same chromatographic profile of amino acids.